Isolation and Identification of Air Borne Fungal Spores and Fragments in Buildings within Usmanu Danfodiyo University Sokoto, Nigeria - Shinkafi Sa’adatu Aliyu; Aliyu Gambo (Aceh International Journal of Science and Technology)
Abstract - Indoor air contains a complex mixture of microorganisms, microorganism fragments, and by products such as molds, bacteria, endotoxins, mycotoxins, and volatile microbial organic compounds. Airborne fungi and bacteria can be toxic, allergenic and/or infectious. A research was conducted to determine the number and types of airborne fungal spores in Buildings of Usmanu Danfodiyo University Sokoto, Nigeria. Five (5) areas were chosen within the University for the Survey, these were student Hostel, Staff Quarters, Botanical garden, Microbiology laboratory and city campus of Usmanu Danfodiyo University. . A total number of fifteen (15) petri dishes containing potato dextrose agar each were vertically placed in each sampler and exposed at end of each height and site for 10 and 20 minutes respectively.  A total of thirteen (13) different fungal specie were identified namely; Aspergillus niger, A. flavus, A fumigates, A. ustus, A. terreus, Fusarium solani, F. oxysporum, Alterneria altenata, Rhizopus oryzae,  R. stolonifer, Helminthosporum sp., Penicillum candidum and Absedia corymbifera. Aspergillus niger had the highest frequency of occurrence of (14.9%), Helminthosporus species had the least frequency of occurrence of (1.5%). Conclusively it was observed that the concentration of fungal spores was high in the upper surface than the ground level at the time of the survey.